Lifestyle Dan Trust Pengaruhnya Terhadap Keputusan Pemesanan Taxi Online - Tri Endi Ardiansyah; Abdul Rauf; Serli Maryana (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
Along by the development of information technology have been stimulated change of customers behavior and this encourages the development of virtual transaction service platforms. Nowadays, customer habits that are formed from lifestyle and encouragement of trust in digital transactions cause people to prefer to transact using online applications, especially in using online taxi services. In addition to being simple, safe, and practical, the selling prices offered are more competitive prefer to offered by conventional companies. Gojek Indonesia is one of Super Apps that famous in Indonesia with sub-brand GoCar. The research was purposed of analyzing the lifestyle and trust of customers and their relationship on decisions to use online taxi services by case study on users of Gojek (GoCar). The research method used is a quantitative with multiple linear regression analysis techniques. The results of the study indicate that lifestyle and trust significantly affect the decision to order taxi online on Gojek (GoCar). Thus encouraging an increase in the value of online taxi booking decisions and the higher the value of lifestyle and trust, the higher the decision. Ordering taxi services online.